PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) DALAM PENDIDIKAN AGAMA HINDU KELAS VIII DI MADYAMA WIDYALAYA JNANA DHARMA SASTRA KECAMATAN BUSUNG BIU KABUPATEN BULELENG - Ni Putu Ratna Utami; Ferdinandus Nanduq; I Gede Dedy Diana Putra (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to examine the implementation of the STAD (Student Teams Achievement Divisions) cooperative learning model in the eighth-grade Hindu Religious Education course at Madyama Widyalaya Jnana Dharma Sastra, Buleleng. The research background stems from a monotonous, teacher-centered learning process that results in suboptimal student participation and interaction. Therefore, an innovative participatory learning model is highly needed to facilitate student cooperation and active engagement within groups. This research employs a qualitative approach to thoroughly investigate the dynamics of learning implementation. Data were collected through classroom observations, in-depth teacher interviews, and documentation studies. The analysis focuses on the planning, execution, learning interactions, and evaluation processes of STAD. Furthermore, the study examines the obstacles educators face and their problem-solving efforts in managing heterogeneous learning groups. The findings indicate that implementing the STAD model positively creates a more active, collaborative, and student-centered classroom atmosphere. Through heterogeneous group discussions and individual quizzes, students' courage to express opinions and their learning responsibilities have significantly improved. Teachers successfully overcame class management obstacles by developing specialized STAD-based lesson plans and providing more contextual learning media.